Interactions between tradition and modernism in Serbian church music of the 20th century - Moody, Ivan (Muzikološki zbornik, 2011)
This paper discusses the question of 'moderate' or 'moderated' modernism in relation to 20thcentury Serbian Church music, concluding that its influence in dialogue regarding with Orthodox spirituality and concerns with liturgical art was not only positive but is far from being exhausted.
Keywords: cerkvena glasba; church music; modernism; modernizem; Serbia; Srbija